2001
DOI: 10.1002/1099-0836(200101/02)10:1<29::aid-bse268>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

The objectivity of corporate environmental reporting: a study of Finnish listed firms' environmental disclosures

Abstract: This study examines the objectivity of Finnish listed companies' environmental reporting in their ordinary annual reports during the period 1985–1996. We study the firms' practice to disclose negative versus positive environmental events that are ex ante publicly known. As regards the entire research period, the results show that the environmental reporting of the sample firms cannot be considered objective, since the proportional share of negative events reported was negligible compared to the respective perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…Niskanen et al, 2001). The results indicate that companies view waste management activities overwhelmingly positively, yielding positive results in all nine categories and the highest scores in eight of them.…”
Section: Semantic Orientationmentioning
confidence: 87%
See 2 more Smart Citations
“…Niskanen et al, 2001). The results indicate that companies view waste management activities overwhelmingly positively, yielding positive results in all nine categories and the highest scores in eight of them.…”
Section: Semantic Orientationmentioning
confidence: 87%
“…The prevalence of corporate environmental disclosures in different industries or countries has been examined in both snapshot and longitudinal analyses, including studies on Australia Gordon, 1996), Finland (Niskanan andNeiminen, 2001), France (Cormier and Magnan, 2003), the United Kingdom (Campbell, 2003), Europe, Japan and the US (Kolk, 2005). Frequently, an industry's environmental impact positively correlates with its degree of environmental disclosure (Deegan and Rankin, 1996;Kolk et al, 2001;Gray et al, 2001;.…”
Section: Corporate Environmental Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale behind analyzing news before other data types is that news is generated from topics on social, corporate, government, and national issues in which the public may be interested [120]. Furthermore, it is generated by a third party, which means it is more likely to be objective than reports compiled by a firm [121,122].…”
Section: Datamentioning
confidence: 99%
“…After studying the annual reports of Finnish companies published between 1985 and 1996, Niskanen and Neiminen (2001) concluded that:…”
Section: Corporate Environmental Accountabilitymentioning
confidence: 99%